A modified polyurethane acrylate, its preparation method and application
By covalently introducing biphenyl rigid and sulfide flexible structural units into the main chain of polyurethane acrylate molecules, the problem of balancing heat resistance and flexibility under high temperature conditions is solved, achieving a synergistic improvement in high heat resistance and high flexibility, which is suitable for bonding motor cores.
Patent Information
- Application Number
- CN202611400627.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-09-10
- Publication Date
- 2026-11-06
AI Technical Summary
Existing polyurethane acrylates cannot simultaneously achieve both heat resistance and flexibility under high-temperature conditions, resulting in a decrease in the bonding strength of the motor core and failing to meet the requirements for long-term service.
By covalently introducing biphenyl rigid structural units and thioether flexible structural units into the main chain of polyurethane acrylate molecules, heat resistance, flexibility and interfacial adhesion are simultaneously improved through intramolecular synergistic effects.
It achieves a heat aging retention rate of up to 90.2% at 150℃, an impact strength of 14.5 kJ/m2, and an adhesion level of 0, breaking the technical prejudice of rigidity versus flexibility, and is suitable for interlayer bonding of motor cores.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] This invention relates to the field of polymer materials technology, and particularly to a modified polyurethane acrylate, its preparation method and application, especially to a polyurethane acrylate in which rigid biphenyl structural units and flexible structural units containing sulfide bonds are covalently bonded in the same molecular backbone, and its application in high-temperature resistant adhesives. Background Technology
[0002] Polyurethane acrylate (PUA) is a high-performance polymer material that combines the flexibility and abrasion resistance of polyurethane with the rapid curing properties of acrylate. It is widely used in adhesives, coatings, inks, and 3D printing. In motor core bonding applications, PUA is widely used as the base resin due to its excellent adhesion to metal substrates and rapid curing capability. However, the internal temperature of motors can reach over 150°C during long-term operation. Under these high-temperature conditions, conventional PUA experiences intensified molecular chain segment movement and a significant decrease in cohesive strength, leading to a substantial reduction in bond strength and making it difficult to meet long-term service requirements. Therefore, how to significantly improve the heat resistance of PUA while maintaining its rapid curing characteristics and good toughness has become a pressing technical challenge in this field.
[0003] To improve the heat resistance of polyurethane (PUA), those skilled in the art first consider introducing rigid aromatic monomers into the molecular structure, such as replacing aliphatic diisocyanates with benzene ring-containing diisocyanates, utilizing the rigid structure of the benzene ring to increase the glass transition temperature of the polymer. However, the rigidity enhancement effect of a single benzene ring is limited, and it is still difficult to meet the requirements under long-term thermal aging conditions above 150°C. Based on this, introducing a more rigid biphenyl structure has become a direction for improvement. Due to its rigid large π-conjugated system, the biphenyl structure has higher rigidity and thermal stability than a single benzene ring, and it has been used in the synthesis of liquid crystal polyurethane to improve the thermal properties of the material. However, while simply introducing a rigid biphenyl structure can improve heat resistance, it leads to excessive rigidity of the molecular chain, brittle adhesive layer, and a significant decrease in impact resistance, making it difficult to directly apply to the bonding of motor cores that need to withstand vibration and impact.
[0004] Meanwhile, techniques for improving the toughness of PUA by introducing flexible segments have also attracted attention. Flexible segments containing thioether bonds possess low rotational barriers, which can impart good flexibility to polymers. For example, 2,2′-thiodiethanol has been reported as a chain extender in the preparation of polyurethane elastomers. However, thioether bonds are less stable than carbon-carbon bonds in high-temperature, oxygen-rich environments, and those skilled in the art generally consider them unsuitable for applications requiring long-term high-temperature resistance.
[0005] Therefore, rigidity enhancement and flexibility improvement are considered contradictory directions in existing technologies. In the field of polymer materials, stiffness, strength, and toughness are generally recognized as mutually restrictive mechanical properties—introducing rigid structures can improve modulus and heat resistance, but inevitably leads to a decrease in toughness. For example, in elastomers and gels, "dense cross-linking points endow the material with high stiffness, but at the same time cause low toughness; this phenomenon is also known as the 'stiffness-toughness conflict.'" This understanding has persisted for nearly two centuries since the invention of vulcanized rubber in 1839 and is widely accepted by those skilled in the art. Based on this, there is a common technical bias in the field of "rigidity and flexibility antagonism," that is, the belief that simultaneously introducing rigid and flexible units into the same molecule will cause the properties to cancel each other out.
[0006] Therefore, there is currently a lack of a polyurethane acrylate modification scheme that can simultaneously take into account heat resistance, flexibility, and interfacial adhesion. Summary of the Invention
[0007] To address the aforementioned technical problems, the main objective of this invention is to provide a modified polyurethane acrylate and its preparation method. By simultaneously covalently introducing biphenyl rigid structural units and thioether flexible structural units into the same polyurethane acrylate molecular backbone, and utilizing their intramolecular synergistic effect, this invention overcomes the technical bias of "rigidity and flexibility antagonism" in the field, achieving simultaneous improvement in heat resistance, flexibility, and interfacial adhesion. This invention also provides the application of this modified polyurethane acrylate in adhesives.
[0008] To achieve the above objectives, the present invention provides the following technical solution: This invention provides a method for preparing modified polyurethane acrylate, characterized by comprising the following steps: S1. Add the biphenyl glycol monomer and the diol monomer containing the sulfide bond to the reactor, evacuate at 105-115°C, and then stir and dehydrate for 2-2.5 hours to make the material melt uniformly and without any bubbles overflowing. Stop evacuating and fill with dry nitrogen to atmospheric pressure to obtain the melt. S2. Cool the melt obtained in step S1 to 70-80°C, add the catalyst, and stir for 10-15 minutes to disperse the catalyst evenly. Then add diisocyanate and stir the reaction at 80-90°C under nitrogen atmosphere for 3-5 hours to obtain isocyanate-terminated prepolymer. S3. Cool the isocyanate-terminated prepolymer obtained in step S2 to 55-60°C, add a polymerization inhibitor, stir for 10-15 minutes to disperse the polymerization inhibitor evenly, then add a hydroxyl compound containing double bonds, and then stir and react at 60-70°C under nitrogen atmosphere for 3-5 hours to obtain modified polyurethane acrylate. The modified polyurethane acrylate contains both biphenyl structural units introduced by biphenyl glycol monomers and thioether structural units introduced by diol monomers containing thioether bonds in its molecular backbone, and the molecular chain ends contain olefinic unsaturated double bonds that can be polymerized by free radicals.
[0009] In its design, this invention covalently bonds two structural units with opposite properties in the main chain of polyurethane acrylate: the biphenyl structure provides a rigid framework and high-temperature resistance to deformation, while the thioether structure provides flexible segments, stress buffering capacity, and metal coordination adsorption capacity. The two are not simply a superposition of properties, but rather a synergistic enhancement achieved through a "rigid-flexible" molecular design.
[0010] In some embodiments, polytetrahydrofuran ether diol is also added in step S1, and the molar ratio of polytetrahydrofuran ether diol to biphenyl glycol monomer is (0.1-0.4):1.
[0011] In some embodiments, the biphenyl glycol monomer is 4,4′-dihydroxybiphenyl; and the thioether-containing diol monomer is 2,2′-thiodiethanol.
[0012] In some embodiments, the molar ratio of the biphenyl glycol monomer to the diol monomer containing a sulfide bond is 1:(0.6 to 1.0).
[0013] Preferably, the molar ratio of the biphenyl glycol monomer to the diol monomer containing a sulfide bond is 1:0.8.
[0014] In some embodiments, the diisocyanate is isophorone diisocyanate; and the hydroxyl compound containing a double bond is hydroxyethyl methacrylate or hydroxyethyl acrylate.
[0015] The improvement in the effect of introducing olefinic unsaturated double bonds from hydroxyethyl methacrylate or hydroxyethyl acrylate in this invention is that the hydroxyl groups in the hydroxyethyl methacrylate or hydroxyethyl acrylate molecules may react with the isocyanate groups at the end of the prepolymer. At the same time, introducing free radical polymerizable olefinic double bonds into the end of the molecular chain gives it a higher space for reactivity regulation and better storage stability.
[0016] In some embodiments, the molar ratio of the diisocyanate to the biphenyl glycol monomer is (2.8–3.3):1.
[0017] Preferably, the molar ratio of the diisocyanate to the biphenyl glycol monomer is 3.0:1.
[0018] In some embodiments, the molar ratio of the double-bonded hydroxyl compound to the biphenyl glycol monomer is (1.6–2.4):1.
[0019] Preferably, the molar ratio of the hydroxyl compound containing the double bond to the biphenyl glycol monomer is 2.0:1.
[0020] In some embodiments, the catalyst is dibutyltin dilaurate or triethylamine; the polymerization inhibitor is p-hydroxyanisole.
[0021] In some embodiments, the amount of catalyst added is 0.2 to 0.4 wt% of the total mass of the modified polyurethane acrylate.
[0022] In some embodiments, the amount of the polymerization inhibitor added is 0.22 to 0.27 wt% of the hydroxyl compound containing double bonds.
[0023] The method for preparing modified polyurethane acrylate in this application selects to carry out the reaction under an inert gas in steps S2 and / or S3 in order to suppress the oxidation side reaction generated during the reaction process.
[0024] In another aspect, the present invention provides a modified polyurethane acrylate obtained by the above preparation method.
[0025] In another aspect, the present invention provides the application of modified polyurethane acrylate in adhesives.
[0026] Compared with the prior art, the present invention has the following beneficial effects: (1) This invention achieves a 90.2% heat aging retention rate of 150℃×500h and 14.5kJ / m³ by simultaneously covalently bonding biphenyl rigid structural units and thioether flexible structural units in the main chain of polyurethane acrylate molecules. 2 The impact strength (see Example 1) achieved a synergistic effect of rigidity and flexibility at the molecular level, breaking the technical prejudice in the field that "rigidity enhancement inevitably sacrifices toughness." The test results compared with those of physical mixing (Comparative Example 6) further proved the synergistic enhancement effect of biphenyl and thioether in the same molecular chain. At the same time, the present invention determined that the optimal molar ratio range of biphenyl glycol to diol containing thioether bonds is 1:(0.6~1.0). By comparing the performance with Comparative Example 4, it was proved that this molar ratio is the key parameter that determines the overall performance of the final material.
[0027] (2) The present invention enhances the physical adsorption and mechanical anchoring effect on the metal surface through the rigid planar structure of biphenyl. At the same time, the lone pair electrons of sulfur atoms in the thioether bond have a coordination adsorption effect on the metal surface. The two mechanisms work together on the same interface, so that the adhesion reaches level 0 (the highest level of the cross-cut method), which is significantly better than the comparative example containing only a single modification unit.
[0028] (3) The preparation method of the present invention adopts the conventional polyurethane prepolymer synthesis process. All raw materials are commercially available. The reaction conditions are mild and no special high pressure or high vacuum equipment is required. It is highly compatible with existing polyurethane acrylate production equipment and is easy to realize industrial production.
[0029] (4) The thermosetting adhesive prepared by the present invention does not require on-site mixing, is easy to operate, and is stable in storage, and is fully compatible with the cycle time requirements of automated production lines for bonding between motor core layers. Detailed Implementation
[0030] The technical solution of the present invention will be clearly and completely described below with reference to specific embodiments. However, those skilled in the art will understand that the embodiments described below are some embodiments of the present invention, but not all embodiments, and are only used to illustrate the present invention, and should not be regarded as limiting the scope of the present invention. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention. Where specific conditions are not specified in the embodiments, conventional conditions or conditions recommended by the manufacturer shall be followed. Where the manufacturers of reagents or instruments are not specified, they are all conventional products that can be purchased commercially.
[0031] Unless otherwise specified, those skilled in the art may select from the following post-processing operations such as "mixing", "vacuum", "heating", "cooling", and "stirring" according to actual conditions, without further limitation.
[0032] Example 1 A method for preparing modified polyurethane acrylate includes the following steps: S1. Add 0.10 mol 4,4′-dihydroxybiphenyl, 0.08 mol 2,2′-thiodiethanol and 0.02 mol polytetrahydrofuran ether diol (Mn≈1000) to the reactor, evacuate at 110℃, and then stir and dehydrate at 300 r / min for 2.3 hours until the material is uniformly melted and no bubbles overflow. Stop evacuating and purge with dry nitrogen to atmospheric pressure to obtain the melt. S2. Cool the melt obtained in step S1 to 75°C, add 0.42 g of dibutyltin dilaurate, and stir at 400 r / min for 13 minutes to disperse the dibutyltin dilaurate evenly. Then add 0.30 mol of isophorone diisocyanate at a feeding rate of 4 g / min. Then continue stirring and reacting at 85°C under nitrogen atmosphere for 4 hours to obtain isocyanate-terminated prepolymer. S3. Cool the isocyanate-terminated prepolymer obtained in step S2 to 58°C, add 0.06 g of p-hydroxyanisole, stir at 400 r / min for 13 minutes to disperse the p-hydroxyanisole evenly, then add 0.20 mol of hydroxyethyl methacrylate at a feeding rate of 4 g / min, and then continue stirring and reacting at 65°C under nitrogen atmosphere for 4 hours to obtain modified polyurethane acrylate.
[0033] Example 2 A method for preparing modified polyurethane acrylate includes the following steps: S1. Add 0.10 mol 4,4′-dihydroxybiphenyl, 0.06 mol 2,2′-thiodiethanol and 0.04 mol polytetrahydrofuran ether diol (Mn≈1000) to the reactor. Vacuum the reactor at 105℃ and then stir and dehydrate at 300 r / min for 2 hours until the material is uniformly melted and no bubbles overflow. Stop vacuuming and purge with dry nitrogen to atmospheric pressure to obtain the melt. S2. Cool the melt obtained in step S1 to 80°C, add 0.54 g of triethylamine, and then stir at 400 r / min for 15 minutes to disperse the triethylamine evenly. Then add 0.28 mol of isophorone diisocyanate at a feeding rate of 2 g / min. Then continue stirring and reacting at 90°C under nitrogen atmosphere for 5 hours to obtain isocyanate-terminated prepolymer. S3. Cool the isocyanate-terminated prepolymer obtained in step S2 to 60°C, add 0.05 g of p-hydroxyanisole, stir at 400 r / min for 15 minutes to disperse the p-hydroxyanisole evenly, then add 0.16 mol of hydroxyethyl acrylate at a feeding rate of 2 g / min, and then continue stirring and reacting at 70°C under nitrogen atmosphere for 5 hours to obtain modified polyurethane acrylate.
[0034] Example 3 A method for preparing modified polyurethane acrylate includes the following steps: S1. Add 0.10 mol 4,4′-dihydroxybiphenyl, 0.10 mol 2,2′-thiodiethanol and 0.01 mol polytetrahydrofuran ether diol (Mn≈1000) to the reactor. Vacuum the reactor at 115℃, and then stir and dehydrate at 300 r / min for 2.5 hours until the material is uniformly melted and no bubbles overflow. Stop vacuuming and purge with dry nitrogen to atmospheric pressure to obtain the melt. S2. Cool the melt obtained in step S1 to 70°C, add 0.29 g of dibutyltin dilaurate, and stir at 400 r / min for 10 minutes to disperse the dibutyltin dilaurate evenly. Then add 0.33 mol of isophorone diisocyanate at a feeding rate of 5 g / min. Then continue stirring and reacting at 80°C under nitrogen atmosphere for 3 hours to obtain isocyanate-terminated prepolymer. S3. Cool the isocyanate-terminated prepolymer obtained in step S2 to 55°C, add 0.07 g of p-hydroxyanisole, stir at 400 r / min for 10 minutes to disperse the p-hydroxyanisole evenly, then add 0.24 mol of hydroxyethyl methacrylate at a feeding rate of 5 g / min, and then continue stirring and reacting at 60°C under nitrogen atmosphere for 3 hours to obtain modified polyurethane acrylate.
[0035] Example 4 A method for preparing modified polyurethane acrylate, the specific implementation method is the same as in Example 1, except that polytetrahydrofuran ether diol is not added, and 2,2′-thiodiethanol is used to replace polytetrahydrofuran ether diol in an equimolar amount.
[0036] Comparative Example 1 A conventional method for preparing polyurethane acrylate, the specific implementation method is the same as in Example 1, except that polytetrahydrofuran ether diol is used to replace 4,4′-dihydroxybiphenyl and 2,2′-thiodiethanol, and the molar amount of polytetrahydrofuran ether diol is the total molar amount of 4,4′-dihydroxybiphenyl and 2,2′-thiodiethanol.
[0037] Comparative Example 2 A method for preparing modified polyurethane acrylate, the specific implementation method is the same as in Example 1, except that 2,2′-thiodiethanol is replaced with an equimolar amount of polytetrahydrofuran ether diol.
[0038] Comparative Example 3 A method for preparing modified polyurethane acrylate, the specific implementation method is the same as in Example 1, except that an equimolar amount of polytetrahydrofuran ether diol is used to replace 4,4′-dihydroxybiphenyl.
[0039] Comparative Example 4 A method for preparing modified polyurethane acrylate, the specific implementation method is the same as in Example 1, except that the amount of 2,2′-thiodiethanol added is 0.15 mol, so that the molar ratio of biphenyl glycol monomer to diol monomer containing thioether bond is 1:1.5.
[0040] Comparative Example 5 A method for preparing modified polyurethane acrylate, the specific implementation method is the same as in Example 1, except that the amount of isophorone diisocyanate added is 0.25 mol, so that the molar ratio of diisocyanate to biphenyl glycol monomer is 2.5:1.
[0041] Comparative Example 6 A method for preparing physically blended modified polyurethane acrylate includes the following steps: The modified polyurethane acrylate prepared in Comparative Example 1 and the modified polyurethane acrylate prepared in Comparative Example 2 were added to a high-speed disperser at a molar ratio of 1:0.8. The mixture was stirred at 1000 r / min for 30 min at 60°C to ensure uniform mixing and to obtain a physically blended polyurethane acrylate.
[0042] Sample preparation The sample preparation method, by weight, includes the following steps: A1. Take 100 parts of polyurethane acrylate, 20 parts of trimethylolpropane triacrylate, 3 parts of dicumyl peroxide, 0.08 parts of p-hydroxyanisole, 1.5 parts of γ-methacryloyloxypropyltrimethoxysilane and 3 parts of fumed silica prepared in each example or comparative example, add them to a planetary stirred tank under light-protected conditions, and vacuum stir at 300 r / min for 45 minutes at 45°C until the mixture is homogeneous, transparent or semi-transparent viscous. Remove and seal to obtain the adhesive. A2. Apply the adhesive prepared in step A1 directly to the bonding surface of the electrical steel sheet (100mm×100mm×10mm), control the adhesive layer thickness to be 0.15mm, and then take another electrical steel sheet to bond it to obtain the adhesive sample. A3. Place the coated sample in a hot press and cure it for 60 seconds at 100℃ and 1.0 MPa pressure. Then remove it and place it at room temperature for 24 hours to obtain the sample.
[0043] Performance testing: 1. Tensile shear strength test: Refer to GB / T 7124-2008 for testing; install the electrical steel sheet lapped specimen on the tensile testing machine, apply tension at a loading rate of 5 mm / min, record the maximum load when the specimen fails, test 5 specimens in each group, and take the arithmetic mean.
[0044] 2. Heat aging strength retention test: After aging the lap joint sample in a constant temperature drying oven at 150℃ for 500 h, remove it and allow it to cool naturally to room temperature. Then, test the tensile shear strength according to GB / T 7124-2008. Strength retention rate = (strength after aging / strength before aging) × 100%.
[0045] 3. Impact strength test: Refer to GB / T 6328-1999 for testing; cast the adhesive into standard impact specimens (80mm×10mm×4mm), and use a cantilever beam impact testing machine to test the unnotched impact strength. Test 5 specimens in each group and take the arithmetic mean.
[0046] 4. Adhesion Test: Refer to GB / T 9286-2021 for testing; use a cross-cut tester to draw 1mm×1mm squares (100 squares) on the cured adhesive layer, adhere it with pressure-sensitive adhesive tape, and then peel it off. The grade is determined by the percentage of peeled area. Grade 0 (the cut edges are completely smooth, with no chips falling off); Level 1 (detachment area ≤ 5%) Level 2 (5% < detachment area ≤ 15%) Level 3 (15% < detachment area ≤ 35%) Level 4 (35% < detachment area ≤ 65%) Level 5 (detachment area > 65%).
[0047] The samples prepared in Examples 1-4 and Comparative Examples 1-6 were tested according to the above-described performance testing methods, and the test results are shown in Table 1.
[0048] Table 1
[0049] According to the performance test data in Table 1 above, Examples 1 to 3 all exhibit good overall performance, with Example 1 showing the best overall performance: room temperature shear strength of 18.9 MPa, strength retention rate of 90.2% after 500 h of heat aging at 150℃, and impact strength of 14.5 kJ / m. 2 The adhesion was rated at level 0. Compared with Examples 1 to 3, the impact strength and heat aging retention rate of Example 4 were slightly reduced, indicating that an appropriate amount of polytetrahydrofuran ether diol as an auxiliary flexible segment can further optimize the flexibility of the system without significantly sacrificing heat resistance, so as to achieve a better balance of comprehensive performance.
[0050] By comparing Example 1 with Comparative Examples 1, 2, and 3, Comparative Example 1, without any modification, exhibits a room temperature shear strength of 14.2 MPa, a heat aging strength retention rate of 45.6%, and an impact strength of 18.5 kJ / m. 2 The first example exhibits the worst overall performance; while the second example, although possessing a heat resistance of 87.2%, suffers from an impact strength of only 6.8 kJ / m² due to the lack of flexible compensation from the sulfide. 2 The adhesive layer was noticeably brittle; compared to Comparative Example 3, although it had 16.2 kJ / m2 It has high impact strength and high toughness, but due to the lack of a rigid skeleton provided by biphenyl, its heat resistance is severely insufficient, only 58.3%; compared with Comparative Examples 2 and 3, Example 1 simultaneously achieves high heat resistance (90.2%) and high toughness (14.5 kJ / m). 2 This demonstrates that the covalent coexistence of biphenyl and thioether structures in the same molecular backbone is not a simple superposition of properties, but rather a synergistic enhancement achieved through a "rigid-flexible" molecular design.
[0051] By comparing with Comparative Example 4, which used a molar ratio of biphenyl glycol monomer to sulfide-containing diol monomer of 1:1.5, the impact strength of Comparative Example 4 was 15.3 kJ / m compared to Examples 1-3. 2 However, the heat aging retention rate decreased to 84.8%, which indicates that when the proportion of sulfide increases, the rigid framework provided by the biphenyl structure is excessively diluted. Therefore, it is proven that the molar ratio range of biphenyl glycol monomer and sulfide-containing diol monomer selected in Examples 1 to 3 of the present invention is a preferred range. At the same time, the molar ratio of 1:0.8 is the optimal ratio for the functional synergy of the biphenyl structure and the sulfide structure.
[0052] Compared with Comparative Example 5, the amount of diisocyanate added was too low, with a molar ratio of diisocyanate to biphenyl glycol of only 2.5:1. This resulted in a room temperature shear strength of only 12.6 MPa and a heat aging retention rate of only 52.1% in the performance tests. This was due to insufficient growth of the prepolymer molecular chains and insufficient chain segment length. At the same time, the amount of double-bonded hydroxyl compounds during end-capping was excessive relative to the residual isocyanate groups. The residual hydroxyl compounds were released during the curing process, which damaged the crosslinking density and cohesive strength of the adhesive layer. This proves that the molar amount of diisocyanate is a key process parameter to ensure the regularity of the prepolymer structure and the excellent performance of the final product. The molar ratio of diisocyanate to biphenyl glycol is within the range selected in this invention to ensure that the prepolymer has sufficient degree of polymerization and a regular end-capping structure.
[0053] A comparison between Example 1 and Comparative Example 6 demonstrates that the modified polyurethane acrylate prepared by physical blending exhibits microscopic phase separation between the biphenyl-modified rigid segments and the sulfide-modified flexible segments, making uniform dispersion at the molecular level impossible. This results in amplified interface defects and accelerated performance degradation during long-term thermal aging, with a thermal aging strength retention rate of only 68.5% and an impact strength of only 10.2 kJ / m. 2 This demonstrates the irreplaceable nature of the present invention in achieving molecular-level synergy through covalent bonding.
[0054] The above description is merely a preferred embodiment of the present invention and is not intended to limit the present invention in any way. Although the present invention has been disclosed above with reference to preferred embodiments, it is not intended to limit the present invention. Any person skilled in the art can make some modifications or alterations to the above-disclosed technical content to create equivalent embodiments without departing from the scope of the present invention. Any simple modifications, equivalent changes, and alterations made to the above embodiments based on the technical essence of the present invention without departing from the scope of the present invention shall still fall within the scope of the present invention.
Claims
1. A method for preparing modified polyurethane acrylate, characterized in that, Includes the following steps: S1. Add the biphenyl glycol monomer and the diol monomer containing the sulfide bond to the reactor, evacuate at 105-115°C, and then stir and dehydrate for 2-2.5 hours to make the material melt uniformly and without any bubbles overflowing. Stop evacuating and fill with dry nitrogen to atmospheric pressure to obtain the melt. S2. Cool the melt obtained in step S1 to 70-80°C, add the catalyst, and stir for 10-15 minutes to disperse the catalyst evenly. Then add diisocyanate and stir the reaction at 80-90°C under nitrogen atmosphere for 3-5 hours to obtain isocyanate-terminated prepolymer. S3. Cool the isocyanate-terminated prepolymer obtained in step S2 to 55-60°C, add a polymerization inhibitor, stir for 10-15 minutes to disperse the polymerization inhibitor evenly, then add a hydroxyl compound containing double bonds, and then stir and react at 60-70°C under nitrogen atmosphere for 3-5 hours to obtain modified polyurethane acrylate. The modified polyurethane acrylate contains both biphenyl structural units introduced by biphenyl glycol monomers and thioether structural units introduced by diol monomers containing thioether bonds in its molecular backbone, and the molecular chain ends contain olefinic unsaturated double bonds that can be polymerized by free radicals.
2. The preparation method according to claim 1, characterized in that, Step S1 further includes the addition of polytetrahydrofuran ether diol, wherein the molar ratio of polytetrahydrofuran ether diol to biphenyl glycol monomer is (0.1-0.4):
1.
3. The preparation method according to claim 1, characterized in that, The biphenyl glycol monomer is 4,4′-dihydroxybiphenyl; the diol monomer containing a sulfide bond is 2,2′-thiodiethanol.
4. The preparation method according to claim 1, characterized in that, The molar ratio of the biphenyl glycol monomer to the diol monomer containing sulfide bonds is 1:(0.6 to 1.0).
5. The preparation method according to claim 1, characterized in that, The diisocyanate is isophorone diisocyanate; the hydroxyl compound containing a double bond is hydroxyethyl methacrylate or hydroxyethyl acrylate.
6. The preparation method according to claim 1, characterized in that, The molar ratio of the diisocyanate to the biphenyl glycol monomer is (2.8–3.3):
1.
7. The preparation method according to claim 1, characterized in that, The molar ratio of the hydroxyl compound containing double bonds to the biphenyl glycol monomer is (1.6–2.4):
1.
8. The preparation method according to claim 1, characterized in that, The catalyst is dibutyltin dilaurate or triethylamine; the polymerization inhibitor is p-hydroxyanisole.
9. A modified polyurethane acrylate obtained by the preparation method according to any one of claims 1 to 8.
10. The use of the modified polyurethane acrylate of claim 9 in an adhesive.
